ANALISIS SITASI HADITS PADA TESIS MAGISTER PRODI HUKUM KELUARGA KONSENTRASI TAFSIR HADITS UIN SUSKA RIAU - Hasanah, Rusydatul; Sudiar, Nining; Amelia, Vita (UIN Imam Bonjol Padang, 2021)
This study aimed to analyze the citation of hadith, frequency of using hadith, history and type of hadith that are ofted be cited by narrators at the master students' theses of family law study program, specifically hadith interpretation concentration of UIN Suska Riau. The method of this study was descriptive statistic. Data collection techniques were observation and documentation. The result of this study indicates the number of theses from hadith interpretation concentration from 2016-2019 as many as 39 theses, with 218 citations from 2.505 citations that listed on bibliography of theses with a percentage 79.48%. From 218 hadiths, hadiths that commonly used as reference were narrated by Bukhori as many as 51 hadiths (23.39%) and type of hadith that commonly be cited was authentic hadith/hadith shohih as many as 168 hadiths